Bangunan Baru Epistemologi Keilmuan Studi Hukum Islam Dalam Merespon Globalisasi - M. Amin Abdullah (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
The term Maqasid al-Syariah is closely linked to the Islamic Studies, especially in the field of the study of Islamic law and Islamic jurisprudence. Some Muslim thinkers, like al-Syatibi (d. 766/1388) in his work al-Muwafaqat and al-Tufi (d.716/1316) in his Risalah are the most representative of them. This article will introduce the development and the enrichment of Maqasid al-Syariah theory in contemporary era via Jasser Audas thought. A difference from the previous theory of Maqasid al-Syariah, this contemporary theory of Maqasid al-Syariah can only be understood and developed, if and only if the Islamic law thinkers can and be able to integrate two different type of scientific approaches, namely Historical approach and Philosophical approach in the same time. Historical approach very keenly alerts the development and the movement of concept, meaning and interpretation in the understanding of Islamic law from the traditional, modern to post-modern era. While philosophical approach utilizes the systems theory a theory which is commonly used in the sciences in the operationalization of those conceptual entities. This systems theory involves six features, namely cognition, wholeness, openness, interconnectedness, multidimensionality, and purposefulness. In the language of scientific and institutional transformation of IAIN (State Islamic Institute) to UIN (State Islamic University) in the Islamic higher education in Indonesia around the year 2000th, this changing scientific outlook is patently well known as integration interconnection of scientific discourse.